Bioactive compounds screening, antimicrobial activities of leave extract from two palatable plants: Piper betle and Murraya koenigii (Curry leaves) - Khin Than, Yee; Mohamad Iswandy, Ibrahim; Nwe, Tin Moe; Thwin, Mya Mya; Lwin, Mar Mar; Aung, Khin Cho; Oo, Ma Saung; Siti Zaleha, Raduan; Yi, Myat San (RJPT, 2023)
Introduction: Piper betle Linn is one of the most commonly used compounding plants for ethno-medical purposes, with its extract generally used in modern products to enrich their functional efficacy. The extraction methods always lead to differences in the antimicrobial efficacy of methanol extracts of bioactive compounds. Purpose: The study was conducted to screen for bioactive compounds and determine their antimicrobial efficacy in a methanol extract of Piper betle and Murraya koenigi leaves from five different regions. Methodology: The phytochemical screening done according to the procedure that is implied in from Patil, et.al, with minor modifications by the researchers of the current study. Antimicrobial activity was determined; efficacy was measured by disc diffusion analysis. Results: Phytochemical screening revealed the presence of saponin, tannin, terpenoids, alkaloids and flavonoids in the extracts. The methanolic extract of betel leaves from all the selected regions except from Bau exhibited antimicrobial activities. Among them, extract from Kuching and Simunjan have no effect on E. coli. The methanolic extract of curry leaves from Kuching, Balai ringai and Bau have antimicrobial activities against Staph aureus and those from Balai ringai is also active against E.coli. Conclusion: Although there were previous reports of phytochemical screening and antimicrobial activities from the extract of these plants, there were still lack of research conducted on the specimens especially from our local community (Sarawak). The outcome of this study will help us to identify the bioactive compounds of the local samples and give us some pictures of their activities on how to ensure these plants can be brought forward based on the origin of the sample. KEYWORDS: Bioactive Compounds Screening, Antimicrobial Activities of Leave Extract, Palatable Plants, Piper betle and Murraya koenigii.